The Effect Of New Habits Adaptation Policies Times Covid-19 On The Utilization Of Antenatal Care Services For Pregnant Mothers In Trimester III In Public Health Bandar Baru, Pidie Jaya Regency - Fitriani; Halum Maisarah Halum; Rahmi Rahmi (Science Midwifery, 2022)
The COVID-19 pandemic has an impact on all sectors including Antenatal care and coverage of pregnancy services have decreased compared to before the Covid-19 pandemic. Data Bandar Baru Health Center in 2021 K1 visits as many as 303 people (60%) and K4 visits were 221 people (44%) with a visit target of 90%. Research Objectives: To determine the effect of new habit adaptation policies the Covid-19 period on the use of antenatal care services for pregnant women third trimester at Bandar Baru Health Center, Pidie Jaya Regency in 2022. Research Methods: Using analytic observational approach cross sectional. The research sample of third trimester pregnant women was 69 people, the study was conducted on 7-24 January 2022, data analysis using univariate and bivariate data using chi square statistical test. Research Results: Utilization of antenatal care services the incomplete category was 38 people (55.1%), the application of the new habit adaptation policy during the Covid-19 pandemic in the inappropriate category was 39 people (56.5%), so that there is an influence on the policy of adapting new habits during the Covid-19 pandemic on the use of antenatal care services with a P Value (0.001) Conclusions and Suggestions: There is an influence of the new habit adaptation policy of the future The Covid-19 pandemic on the use of antenatal care services. It is hoped that health workers can provide information regarding the adaptation of new habits during the Covid-19 period regarding standard procedures for antenatal care services